The New Deal a modern history - Hiltzik, Michael A. (Free Press, 2011)
Franklin Roosevelt's New Deal began as a program of short-term emergency relief measures and evolved into a truly transformative concept of the federal government's role in Americans' lives. More than an economic recovery plan, it was a reordering of the political system that continues to define America to this day. With this book, writer Michael Hiltzik offers fresh insights into this inflection point in the American experience. He shows how Roosevelt, through force of personality, commanded the loyalty of the fiscal conservatives and radical agrarians alike--yet the same character traits that made him a great leader would sow the seeds of the New Deal's end. Understanding the New Deal may be more important today than at any time in the last eight decades. Conceived in response to a devastating financial crisis very similar to America's most recent downturn--the New Deal remade the country's economic and political environment in six years of intensive experimentation, and provided a model for subsequent presidents who faced challenging economic conditions, right up to the present.--From publisher description